Antitrust and consumer enforcement in data markets – Are new theories of harm based on privacy degradation hitting the mark? - Serafino Abate (International Telecommunications Society (ITS), 2018)
The part of the economy that depends, directly or indirectly, fully or partially, on the flow and analysis of data is growing of importance2. Data-driven businesses are spilling over from the online to the offline economy, changing traditional industries. They are set to become pervasive in the coming decade, with the rise of the industrial internet, the development and adoption of AI, and the advent of new, more advanced networks. As a result, it is not surprising to find that antitrust enforcement in data markets is rising, and the nature of it is in part changing. This raises different issues that are relevant for competition policy in general, antitrust enforcement and consumer protection. Firstly, alongside traditional theories of harm, new theories of harm are being tested. Some of the recent enforcement cases based on privacy degradation aim at detecting whether or not some platforms have abused their dominance and exploited their customers in the form of data harvesting which goes behind what is permitted ("data exploitation"). Due to the unique nature of data markets and its economics, these new theories of harm rise issues with respect to remedies that are worth considering further. This working paper focuses on the first aspect, namely to consider whether new exploitative theories of harm based on privacy degradation are plausible...
Keywords: 330